differential equation
posted by farook .
Find the Laplace transform by using the theorem of L{f(ta)H(ta)}=(e^as)F(s)
L{(e^4t)H(t10)}
Respond to this Question
Similar Questions

Math
Using the table Laplace transform, determine the function f (t) of the following functions F (s). F(s)= 1/s^2 + 3s/s^2+9 F(s)= 6/s^2 + 10s+29 F(s)= 1/2s + 8/s^2+4s+8  3/s^2 
CalculusHELP!!!
Find the Laplace transform of: f(t) = cos^(2)(2t) 
Calculus
Find the Laplace transform of: f(t)=t2e^(3t) 
CalculusHELP!!!
Find the inverse Laplace transform of: F(s)=2/s^4 
Calculus
Find the inverse Laplace transform of: F(s)=3/(s4) 
calculus
Solve the DE by using the Laplace transform: x''+x=cos(3t), x(0)=x'(0)=0 
Calculus
Solve the differential equation by using Laplace transforms. Find the particular solution that satisfies them of: y''+2y'+y =4e^(t) 
Differential Equations
Use the Laplace Transform to solve this initial value problem. y''''  8y = 0, y'(0)=63, y''(0)=216, y'''(0)=297 I would really appreciate the help. 
Calc2
Let f(t) be a function defined for all values of t. The Laplace Transform of f(t) is defined by: F(s)= ç[∘,‡](e^st(f(t))dt). If the improper integral exists, Find the Laplace Transform for F(t)=t^2. 
calc 2
(last one) ... Let f(t) be a function defined for all values of t. The Laplace Transform of f(t) is defined by: F(s)= ç[∘,‡](e^st(f(t))dt). If the improper integral exists, Find the Laplace Transform for f(t)= sinhat